Landscape Research of Entrepreneurship Intention - Susanti, Susan; Purnamasari, Imas; Kurjono, Kurjono; Gunawan, Ashari (Universitas Pendidikan Indonesia, 2024)
This study aims to analyze the landscape of research on entrepreneurial intentions over the past five years through bibliometric analysis. Data were collected from the Scopus database, resulting in a total of 56 publications. The results indicate that the publications are widely distributed across various countries, showing significant influence and high levels of international collaboration in this field. The focus of this study includes: 1) entrepreneurial intentions, 2) development and case studies, and 3) international cooperation on entrepreneurial intentions. The findings of this study can serve as a reference for future researchers interested in this theme, providing an understanding of the research focus and setting a trajectory for further studies.